2020
DOI: 10.3389/fimmu.2020.551758
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis Linked to Aberrant Amino Acid Metabolism and Immunosuppressive Amino Acid Catabolizing Enzymes

Abstract: Cardiovascular disease is the leading global health concern and responsible for more deaths worldwide than any other type of disorder. Atherosclerosis is a chronic inflammatory disease in the arterial wall, which underpins several types of cardiovascular disease. It has emerged that a strong relationship exists between alterations in amino acid (AA) metabolism and the development of atherosclerosis. Recent studies have reported positive correlations between levels of branched-chain amino acids (BCAAs) such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 324 publications
(403 reference statements)
3
49
0
Order By: Relevance
“…Thus, identification of metabolic pathways that contribute to the pathogenesis of atherosclerosis, beyond altered lipid metabolism, may lead to the development of novel therapeutics. Recent evidence indicates that dysregulated amino acid metabolism plays a role in atherosclerosis (Grajeda-Iglesias et al, 2018;Nitz et al, 2019;Rom et al, 2018;Zaric et al, 2020). Specifically, lower circulating glycine has been consistently reported in various cardiometabolic diseases, including coronary heart disease (Wittemans et al, 2019), myocardial infarction (Ding et al, 2015), T2D (Guasch-Ferré et al, 2016), metabolic syndrome (Li et al, Cell Reports 36, 109420, July 27, 2021 9 Article ll OPEN ACCESS 2018), obesity (Newgard et al, 2009), and NAFLD (Gaggini et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, identification of metabolic pathways that contribute to the pathogenesis of atherosclerosis, beyond altered lipid metabolism, may lead to the development of novel therapeutics. Recent evidence indicates that dysregulated amino acid metabolism plays a role in atherosclerosis (Grajeda-Iglesias et al, 2018;Nitz et al, 2019;Rom et al, 2018;Zaric et al, 2020). Specifically, lower circulating glycine has been consistently reported in various cardiometabolic diseases, including coronary heart disease (Wittemans et al, 2019), myocardial infarction (Ding et al, 2015), T2D (Guasch-Ferré et al, 2016), metabolic syndrome (Li et al, Cell Reports 36, 109420, July 27, 2021 9 Article ll OPEN ACCESS 2018), obesity (Newgard et al, 2009), and NAFLD (Gaggini et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis, the underlying cause of most CVDs, is a chronic disease of the arteries arising from imbalanced lipid metabolism, a maladaptive immune response, and dysregulated redox homeostasis (Griendling et al, 2016;Moore et al, 2013). While the association between altered lipid metabolism and CVDs is well established, recent evidence indicates that dysregulated metabolism of specific amino acids plays an important role in the pathogenesis of atherosclerosis (Grajeda-Iglesias et al, 2018;Nitz et al, 2019;Rom et al, 2018;Zaric et al, 2020). Among all amino acids, lower circulating glycine is emerging as a common denominator in CVDs and related metabolic comorbidities (Rom et al, 2018), including coronary heart disease (Wittemans et al, 2019), myocardial infarction (Ding et al, 2015), obesity (Newgard et al, 2009), type 2 diabetes (T2D) (Guasch-Ferré et al, 2016), metabolic syndrome (Li et al, 2018), and non-alcoholic fatty liver disease (NAFLD) (Gaggini et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, worldwide epidemiological studies among 61 different population groups in 25 different countries have reported that regular taurine intake through daily consumption of seafood, nuts, soy and milk reduces the prevalence of cardiovascular diseases that include hypertension and hypercholesterolemia [ 94 , 189 , 190 , 191 , 192 ]. While the underlying mechanisms by which taurine attenuates hypertension remain unclear, several in vitro and in vivo studies have suggested the antioxidant activity of taurine in reducing hypertension, which include reducing ROS generation [ 193 , 194 ], improving ATP production [ 195 ] and improving mitochondrial metabolism [ 196 ]. Indeed, hypertension has been largely associated with mitochondrial dysfunction, which includes mitochondrial oxidative stress [ 197 ], alteration of mitochondrial homeostasis and impaired energy production.…”
Section: Clinical Application Of Taurine In Mitochondria-targeted Pathologiesmentioning
confidence: 99%
“…AA metabolism (e.g. Larginine, high arginine and L-tryptophan) is also considered a key regulator of vascular homeostasis (Nitz et al 2019;Zaric et al 2020). A dietary intake high in arginine, taurine and glycine ameliorate atherosclerosis through endothelial remodelling (Zaric et al 2020).…”
Section: Xinnaokang Regulated Liver Metabolism In Mice With Atherosclerosismentioning
confidence: 99%
“…Larginine, high arginine and L-tryptophan) is also considered a key regulator of vascular homeostasis (Nitz et al 2019;Zaric et al 2020). A dietary intake high in arginine, taurine and glycine ameliorate atherosclerosis through endothelial remodelling (Zaric et al 2020). These results indicated that Xinnaokang treatment could improve the liver metabolic function of atherosclerotic mice.…”
Section: Xinnaokang Regulated Liver Metabolism In Mice With Atherosclerosismentioning
confidence: 99%